Teaching About the Nexus Between Law and Society: From Pedagogy to Andragogy - Patricia Easteal (Legal Education Review)
The purpose of this paper is to make an informed contribution to the discussion about appropriate responses to the critical issue of student workload in legal education. This paper will argue that the most appropriate response is to modify aspects of curriculum design. This option can reduce student perceptions of heavy workload without compromising educational outcomes. The paper considers the findings of a project to rigorously explore the issue of student workload and to develop an appropriate response for a postgraduate online practical legal education program. The authors submit that many of the recommendations from the project are potentially transferable to other teaching contexts.